2021
DOI: 10.3390/microorganisms9091832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atrazine on Chernozem Microbial Communities Evaluated by Traditional Detection and Modern Sequencing Technology

Abstract: Atrazine is a long residual herbicide commonly used in maize fields. Although atrazine can effectively control weeds and improve crop yield, long-term application leads to continuous pollution in the agricultural ecological environment, especially in the soil ecosystem, and its impact on soil microorganisms is still not clear. Four methods were used in the experiment to clarify the effect of atrazine on the bacterial populations of cultivated soil layers of chernozem in a cold region in different periods: high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…PPO plays an important role in respiration, and its activity is high in cropland (Khosrozadeh et al, 2022). Atrazine significantly affected the activity of PPO in the soil at different periods (Yang et al, 2021). Hence, their activities may be a useful indicator for evaluating soil quality and health (Floch et al, 2007).…”
Section: Effect Of Tested Fumigants On Ppo Activitymentioning
confidence: 99%
“…PPO plays an important role in respiration, and its activity is high in cropland (Khosrozadeh et al, 2022). Atrazine significantly affected the activity of PPO in the soil at different periods (Yang et al, 2021). Hence, their activities may be a useful indicator for evaluating soil quality and health (Floch et al, 2007).…”
Section: Effect Of Tested Fumigants On Ppo Activitymentioning
confidence: 99%
“…It is known that many herbicide active ingredients disturb the balance of the soil microbial community, while others show no effect [9]. For example, relevant research revealed that atrazine reduced the diversity of bacterial populations in soils cultivated with maize [10]. Moreover, sulfonylurea reduced the abundance of bacteria in the rhizosphere of winter wheat [11], while mesotrione reduced the abundance of soil microbe [12].…”
Section: Introductionmentioning
confidence: 99%